The pricing behaviour of Italian firms: new survey evidence on price stickiness - Silvia Fabiani; Angela Gattulli; Roberto Sabbatini (European Central Bank (ECB), 2004)
This study examines price setting behaviour of Italian firms on the basis of the results of a survey conducted by Banca d'Italia in early 2003 on a sample of around 350 firms belonging to all economic sectors. Prices are mostly fixed following standard mark-up rules, although customer-specific characteristics have a role, in particular in manufacturing and services where price discrimination across customers matters. Rival prices mostly affect pricesetting strategies in industrial firms. In reviewing their prices, firms follow either state-dependent rules or a combination of time and state-dependent ones. Concerning the frequency of price adjustments, a considerable degree of stickiness emerges both at the stage in which firms evaluate their pricing strategies and the stage in which they actually implement the price change. In 2002 most firms changed their price only once. Three alternative explanations of nominal rigidity are ranked highest by the firms interviewed: explicit contracts, tacit collusive behaviour and the perception of the temporary nature of the shock. Prices respond asymmetrically to shocks, depending on the direction of the adjustment (positive vs negative) and the source of the shock (demand vs supply). Real rigidities – captured by the degree of market competition, customers' search costs, the sensitivity of profits to changes in demand – play an important role in determining this asymmetry. Moreover, whereas cost shocks impact more when prices have to be raised than when they have to be reduced, demand decreases are more likely to induce a price change than demand increases.
Keywords: E30; D40; 330; Inflation persistence; nominal rigidity; price-setting; real rigidity; survey data